Neonatal Arterial Tortuosity and Adult Aortic Aneurysm—Is There a Missing Link?—A Case Report - Bharadwaj, Srabani; Chan, Charmaine; Choo Tze Liang, Jonathan; Sanamandra, Sarat Kumar; Fortier, Marielle Valerie; Koh, Ai Ling; Sundararaghavan, Sreekanthan (Frontiers in Pediatrics, 2022)
Abstract: We report a novel case of a full term newborn with nonimmune fetal hydrops and arterial tortuosity mimicking a double aortic arch, and cranial fractures in the immediate neonatal period. The infant had no classic features of neonatal arterial tortuosity syndrome or Loeys Dietz syndrome apart from bilateral inguinal hernia. He also had skeletal manifestations in the form of fractures in the neonatal period without any trauma during birth and without clinical evidence of Osteogenesis Imperfecta. A heterozygous missense variant of uncertain significance was detected in MYH11 gene which is increasingly recognised to be belonging to the familial/hereditary thoracic aneurysm and aortic dissection group of disorders. Fetal hydrops as an association with arterial tortuosity has not been described in the literature. We hypothesize the possible mechanism behind developing fetal hydrops when associated with arterial tortuosity and discuss the genetic and phenotypic heterogeneity of the Familial Thoracic Aortic Aneurysm and Dissection (FTAAD) group of conditions highlighting the unique phenotypic and genotypic presentations. We recommend a high index of suspicion and vigilance in the early detection of such potentially lethal conditions with sequelae also in adulthood.